Factors influencing plastic overconsumption in Japan from consumers’ perspective : A social experiment - Kovalska, Tereza (My University, 2024)
This thesis focuses on obstacles preventing Japanese consumers from reducing their plastic consumption. The purpose of this thesis is to fill a knowledge gap on the issue of plastic, shifting focus from waste management to causes of high plastic waste production from the perspective of Japanese consumers. Moreover, it challenges previous research on the environmental awareness of Japanese consumers. The study is relevant as it offers empirical research stemming from the direct involvement of consumers as they attempt to avoid purchasing anything containing or packaged in plastic for a week, recording the obstacles they have encountered. The study finds that there is a series of socio-cultural factors impacting the preference for plastic material by both manufacturers and consumers. This preference then creates obstacles for consumers which make it extremely difficult for them to avoid plastic material during their purchases. Moreover, the findings suggest that despite a seemingly high environmental awareness of consumers, many the lack essential knowledge and skills to significantly impact the environment with their behavior. The findings can be used to shift the focus of environmental and educational policies. Furthermore, they can help implement effective changes based on consumers’ needs and address the obstacles and their causes as pointed out by this study. How to implement such changes is a question for further research.
Keywords: Japan, plastic, consumption, environmental awareness, consumers, social experiment